WASTE BANK PROGRAM IN SUSTAINABLE DEVELOPMENT EFFORTS OF SEMARANG DISTRICT (Study in Soka Resik Waste Bank, Soka Hamlet, Lerep Village, West Ungaran Sub-District, Semarang Regency) - Setyarini, Shanaz Vindi; Subowo, Ari; Afrizal, Teuku (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Sustainable development is a reference for global development in all development fields in Indonesia, especially those related to environmental sustainability. Solid waste pollution is a crucial problem that harms environmental sustainability, such as odor, water, air, and solid waste pollution. These problems need to be managed effectively with a specific approach, including a waste bank. The Waste Bank is a community empowerment-based effort that involves a Reduce, Reuse, and Recycling program using solid waste as an economic resource. Further, the waste bank program is also changing the paradigm from the